Penentuan Jenis Intervensi Sense Pecahan Calon Guru Berdasarkan Logika Fuzzy - Suwanti, Vivi; Murniasih, Tatik Retno (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2022)
This study aims to describe the implementation of the fuzzy inference system in determining the type of fractional sense intervention for preservice teachers and to make comparisons with conventional assessment techniques. The implementation phase of the research carried out included fuzzy modeling, inference system design, fractional sense test trials on preservice teachers, and comparative analysis. The instruments used in this study included fractional sense test sheets and interview guidelines. Based on comparative analysis, the use of fuzzy applications in determining the type of intervention is more in accordance with the results of qualitative analysis than the calculation of statistical averages. The results of the fuzzy application are more rational and fair in determining the type of intervention than the average calculation. In future research, it is suggested to use various fuzzy methods to compare the best fractional sense intervention decision making.